Beyond the Bullet Points: Teaching the Bible in Norwegian Upper Secondary Religious Education - Hartvigsen, Kirsten Marie (Religious education, 2020)
This qualitative study examines semi-structured interviews with four Norwegian teachers to explore how they teach biblical texts in upper secondary religious education (RE). The theoretical framework combines one model from biblical hermeneutics with one from RE. The former differentiates between the worlds behind, in, and in front of the biblical text, the latter between the universal, common religious, and religion-specific dimensions of religious narratives. Chief findings: All teachers utilize examples from the reception history of the biblical texts; they thus extend Ricoeur’s notion of the world in front of the text. The common religious aspects of biblical texts are mostly overlooked.